CHARACTER ASSOCIATION AND PATH ANALYSIS IN GARLIC (ALLIUM SPP.) GERMPLASM UNDER SUB TROPICAL ENVIRONMENT OF JAMMU - SATESH KUMAR; R.K.SAMNOTRA; MANOJ KUMAR; SHILPI KHAR (The Bioscan, 2015)
Genetic variability of 41 genotypes of garlic collected from different agroclimatic zone of Jammu division was assessed for yield, quality and other agronomic characters. The analysis of variance revealed greater variability for all the traits studied except number of leaves/plant, leaf length, dry matter content, total soluble solids and equatorial diameter. High heritability coupled with high genetic advance as percent of mean was observed for plant height (69.23%), average weight of cloves (66.3%), yield/ hectare (54.00%), leaf length (36.04%), equatorial diameter (32.20%) and average weight of bulbs (74.8%) which lead to additive gene action and their expression and phenotypic selection for their amenability can be brought about. Average bulb weight showed positive and significant correlation with number of leaves/plant, leaf length, average weight of cloves, equatorial diameter, while it was negative and significantly correlated with total soluble solids. Positive direct effect on average weight of bulb was observed for average weight of 10 cloves/bulb (0.950), dry matter (0.575), equatorial diameter (0.419), leaf length (0.127) and plant height (0.222). Therefore it can be inferred from the present study that good scope for garlic improvement in this region is possible through positive selection pressure on suitable traits in desirable genotypes.